A comparison of rat degloving injury models - Altun, Serdar; Orbay, Hakan; Ekinci, Mehmet; Cetinbas, Ahmet; Bal, Ali; Arpaci, Enver; Okur, Mehmet Ihsan (Turkish Assoc Orthopaedics Traumatology, 2017)
Objective: Two different rat models for degloving injury were described in the literature. Our aim in this study is to compare these rat models to determine which one is more reliable and reproducible. Methods: We surgically induced degloving injury on tails and left hindlimbs of Wistar albino rats (n = 8), and sutured the avulsed tissues back in their original positions after a waiting period. We observed the changes in the avulsed flaps every other day for 10 days. At the end of follow-up period we evaluated the lesions in avulsed flaps by macroscopic measurement of necrosis and histological ulcer scoring using the National Pressure Ulcer Advisory Panel (NPUAP) Scale. Results: The average length of necrosis in avulsed tail flaps was 28.42 +/- 3.04 mm, whereas there was no necrosis in avulsed hindlimb flaps (p < 0.05). The average ulcer score of the lesions in tail and left hindlimb were 3.42 +/- 0.78, and 1.28 +/- 0.48, respectively (p < 0.05). Despite the lack of visible necrosis TUNEL staining revealed an increased amount of apoptotic cells in avulsed hindlimb flaps. Literature review revealed a significant variability in previous studies in terms of the amount of necrosis observed in tail degloving injury model. Conclusion: Tail degloving injury model proved to be a more reliable animal model for degloving injuries. However, standardization of the magnitude of degloving force is required to decrease the variability of necrosis observed in the literature. (C) 2017 Turkish Association of Orthopaedics and Traumatology. Publishing services by Elsevier B.V.
Keywords: Degloving injury; Rat; Tail; Hindlimb